Retraction Note: Dishonesty is more affected by BMI status than by short-term changes in glucose - Eugenia Polizzi di Sorrentino; Benedikt Herrmann; Marie Claire Villeval (Scientific Reports, 2021)
Editor's Note: this Article has been retracted; the Retraction Note is available at https://doi.org/10.1038/s41598-020-80528-2.